URGENSI PEMANFAATAN TEKNOLOGI DRONE DALAM PENDAFTARAN TANAH SISTEMATIS LENGKAP GUNA MENINGKATKAN EFISIENSI PEMETAAN LAHAN. - Ziddane Rangga Buana; Dimas Nur Dwianto; Muhammad Rizky Yudhoyono Santoso; Muhammad Adymas Hikal Fikri (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This research examines the urgency of using drone technology in Complete Systematic Land Registration (PTSL) to increase the efficiency of land mapping. Currently, the land registration process in Indonesia still faces various obstacles, especially regarding accuracy and efficiency in land mapping. Drone technology is considered capable of providing innovative solutions by producing accurate spatial data and speeding up the field monitoring process. In this research, a normative juridical method is used to analyze legal provisions regarding land registration in Indonesia and the urgency of using drone technology in complete systematic land registration including potential benefits, as well as challenges faced in its implementation. The research results show that the use of drones in PTSL can not only speed up the land certification process, but also strengthen legal certainty for land owners through more accurate data. It was announced that the use of this technology can support the government's accelerated land certification program more efficiently and effectively, as well as contribute to sustainable development.